Association of phthalates and early menarche in Korean adolescent girls from Korean National Environmental Health Survey (KoNEHS) 2015–2017 - Park, One (Ann Occup Environ Med, 2021)
BACKGROUND: Phthalates are one of renowned endocrine-disrupting chemicals, although inconsistent results are present around their effect on onset of menarche. Our hypothesis is that pre-pubertal exposure to phthalates is associated with acceleration of menarche. METHODS: We analyzed a total of 236 middle school (7th to 9th grade) girls from Korean National Environmental Health Survey 2015–2017. We used multiple linear regression to investigate impact of eight phthalate metabolites on age of menarche. We also conducted logistic regression to evaluate association between phthalate metabolite concentrations and early onset of menarche, adjusting for grade, maternal age of menarche and body mass index (BMI). RESULTS: In linear regression analysis, no significant association was found for any phthalate metabolites. In logistic regression analysis, however, odds ratios (ORs) of early menarche were significantly increased for mono-n-butyl phthalate (MnBP) and for sum of all phthalates. When compared to group with the lowest level, high concentration group for MnBP presented significantly increased odds of early menarche (OR: 2.09; 95% confidence interval [CI]: 1.03, 4.23) after adjusting for grade, maternal age of menarche and BMI. Furthermore, high concentrations of sum of all phthalates were associated with significant increase of OR of early menarche (OR: 2.22; 95% CI: 1.10, 4.49) after adjustment, compared to the lowest concentration group. CONCLUSIONS: Results of our study suggest that exposure to phthalates around puberty may be associated with increased risk of early menarche.